2013
DOI: 10.1080/09602011.2013.784709
|View full text |Cite
|
Sign up to set email alerts
|

Concrete behaviour and reappraisal deficits after a left frontal stroke: A case study

Abstract: Concrete behaviour, the inability to disengage from immediate experience in order to manipulate ideas and thoughts, has long been understood to be a common problem after frontal lobe lesions. However, there has been little consideration of the impact that concreteness may have on emotional functioning, specifically in the use of thinking to manipulate emotional responses. One widely studied emotion regulation strategy is reappraisal, which depends on several frontal lobe related cognitive control processes. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 80 publications
1
51
0
Order By: Relevance
“…Moreover, the ROI group not only showed deficits in REAPPself, but was also the group with most inhibition failures (number of errors) during Go/NoGo tasks. This is of particular interest, as one case study reported that inhibition impairments after a left frontoparietal lesion generated difficulties to spontaneously generate reappraisals (Salas et al, 2013). As previously shown in lesion studies, patients with right PFC lesions typically show inhibition difficulties, reflected by increased error rates in the interference condition of the Stroop task (Vendrell et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the ROI group not only showed deficits in REAPPself, but was also the group with most inhibition failures (number of errors) during Go/NoGo tasks. This is of particular interest, as one case study reported that inhibition impairments after a left frontoparietal lesion generated difficulties to spontaneously generate reappraisals (Salas et al, 2013). As previously shown in lesion studies, patients with right PFC lesions typically show inhibition difficulties, reflected by increased error rates in the interference condition of the Stroop task (Vendrell et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition performance, which is supposed to be a right lateralized function (Garavan et al, 1999), might influence the ability of decreasing automatic negative appraisals, thus constituting a corner pillar for the architecture of reappraisal and especially, REAPPself (Salas et al, 2013, 2014). However, we cannot rule out the influences of depression symptoms, particularly on the down-regulation of valence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in one study, Feeser and colleagues (Feeser, Prehn, Kazzer, Mungee, & Bajbouj, 2014) found that transcranial direct current stimulation to the dorsolateral prefrontal cortex enhanced participants' ability to engage in reappraisal. Other studies have examined the impact of brain damage on emotion regulation (Anderson, Barrash, Bechara, & Tranel, 2006;Salas, Gross, Rafal, Vinas-Guasch, & Turnbull, 2013). Further studies are required to better understand how different brain systems are engaged in the course of successful reappraisal and what goes wrong when regulation fails.…”
Section: The Neural Bases Of Emotion Regulationmentioning
confidence: 96%
“…Professor F's capacity to recognize accurately, and label, basic emotions is preserved for all emotions except disgust. When compared to a sample of 15 ageand education-matched healthy controls (Salas, Gross, Rafal, Viñas-Guasch, & Turnbull, 2013), he does not present significant differences in the total score [t (14) Emotional expressivity (BEQ). Professor F's capacity to express negative and positive emotions, as well as the intensity of his emotional reactions, appears to be in the normal range.…”
Section: Emotion and Personality Assessmentmentioning
confidence: 92%